Supplemental data and results package for Pappalardo et al (2025) publication "Scales of variation in zooplankton communities and monitoring for species of concern in southcentral Alaska" - Paula Pappalardo (21762533) (2025)
# README - FigShare data and results package ## Overview This data package includes input data and results associated with the publication “Scales of variation in zooplankton communities and monitoring for species of concern in southcentral Alaska” by Pappalardo et al. (2025) in ICES Journal of Marine Science. Our study used DNA metabarcoding of plankton samples to assess zooplankton richness and composition in coastal waters. This approach can also monitor species of concern, including planktonic and benthic species with planktonic larvae. Our study used the mitochondrial COI gene to evaluate how factors such as collection date (year, month, week), tidal cycle, and location affect zooplankton community dynamics. We found that seasonality had the greatest impact on species richness and composition, particularly among meroplankton groups, with peaks in abundance in April and May. Eight potentially introduced species were detected, with Oithona davisae appearing in three locations over two years. Our findings indicate that plankton surveys are effective monitoring tools, and the timing of sampling is crucial for detecting larval stages of introduced species. We also offer bioinformatic recommendations to enhance species detection and validation. ## Data The contents of the “data” folder are all needed to run the R code associated with the publication. The “data” folder contents include: 1) __dada2__: includes the sequence tables from the dada2 pipeline and the tracking files. 2) __blast__: includes the BLAST results plus the taxonomy files from each reference database to add higher taxonomy to the blast results. 3) __taxfiles__: includes files to add higher taxonomy to the reference databases. 4) __metadata__: includes: a. the field metadata for each sample, in addition to basic information such as run_name and primers b. the non native status for each metazoan species assessed after checking the literature and occurrence data ## Output from R code The contents of the “output” folder were generated by running the R code associated with the publication. The R code used for data analysis is available in Zenodo (link available in the metadata). The “results” folder contents include: 1. results: includes the final IDs, the phyloseq object, the downloaded occurrence data, and all the parsed datasets for the analysis of different factors. 2. temp-r-objects: includes temporary R objects that could be useful for troubleshooting or that are used in other scripts. 3. filtered-seqtab: includes the filtered OTU tables, the final merged OTU table for analysis, and the fasta file used for BLAST. 4. tables: includes tables used for the MS or the supporting information. 5. figures: includes the figures used for the MS or the supporting information.